2019
DOI: 10.1002/cche.10248
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of enzymatically modified pea protein‐enriched flour treated by different enzymes to varying levels of hydrolysis

Abstract: Background and objectives Air‐classified pea protein‐enriched flour (PPEF) was modified with trypsin, Savinase, papain, and pepsin to achieve 2%–4% and 10%–12% degrees of hydrolysis, and the surface and functional properties of the hydrolyzed products were assessed. Findings Surface hydrophobicity increased from 13.3 to 48.5 A.U. with papain treatment. Surface charge became more electronegative from −12.6 to −19.0 mV with pepsin treatment. However, solubility of hydrolyzed PPEF at all pH values tested (4.0, 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
(70 reference statements)
4
25
2
Order By: Relevance
“…Consequently, a one‐factor analysis of variance (ANOVA) found that hydrolysis did not have a significant ( p < .01) impact on FC relative to the untreated isolate for any of the three pH conditions. Decreases to FC upon following treatment were assumed to be a consequence of increased hydrophobic protein–protein interactions decreasing protein activity at the interfacial layer (Konieczny et al, 2019; Wani et al., 2015). In addition, relatively high levels of deviation prevented significant ( p < .01) differences from being noted between the hydrolysates at pH 4 and 7.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, a one‐factor analysis of variance (ANOVA) found that hydrolysis did not have a significant ( p < .01) impact on FC relative to the untreated isolate for any of the three pH conditions. Decreases to FC upon following treatment were assumed to be a consequence of increased hydrophobic protein–protein interactions decreasing protein activity at the interfacial layer (Konieczny et al, 2019; Wani et al., 2015). In addition, relatively high levels of deviation prevented significant ( p < .01) differences from being noted between the hydrolysates at pH 4 and 7.…”
Section: Resultsmentioning
confidence: 99%
“…However, hydrophobicity did not progressively increase with higher levels of hydrolysis. Increases in hydrophobicity were initially anticipated, as hydrolysis was expected to increase the access of the ANS reagent to the hydrophobic amino acid residues within the interior of the CPI proteins (Humiski & Aluko, 2007; Konieczny et al, 2019). Therefore, the lack of any substantial increase in hydrophobicity following increased enzyme treatment could indicate that the protein molecules had been wholly denatured during sample preparation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations